Mesophotic thermal refuge modelling shows mitigated reductions in fisheries productivity during marine heatwaves - Beran, Hiromi; Datta, Samik; Smith, Robert O.; Woods, Lisa; Ladds, Monique; Bell, James J.; Rogers, Alice (Frontiers in Marine Science, 2025)
The oceans are warming, and marine heatwaves are increasing in frequency, extremity and duration. As ectotherms, fish that experience temperatures above their optimum suffer a host of physiological and demographic impacts, which result in a net negative effect on population biomass and productivity. However, temperatures generally decline with depth, which means that mesophotic ecosystems, found in the ‘twilight zone’ between approximately 30 and 150 m depth, have the potential to act as thermal refuges. While pelagic fishes have flexibility to deepen their distributions in the open ocean, reef fishes are dependent on benthic habitats for structural complexity and food. Mesophotic reefs may therefore be of particular importance as thermal refuges in coastal ecosystems. By analysing 27 years of model-derived temperature-depth data, we found that the intensity, duration and frequency of marine heatwaves were buffered at mesophotic versus euphotic depths at Tawhiti Rahi (the Poor Knights Islands) in Aotearoa, New Zealand. To explore and quantify the importance of this mesophotic thermal refuge we parameterised a temperature-dependent multispecies size-spectrum model for the Poor Knights Islands reef community and ran marine heatwave simulations in the presence and absence of mesophotic reef habitat. Almost all heatwave strengths resulted in biomass and productivity reductions for almost all modelled fish species, but the presence of a mesophotic thermal refuge often reduced or reversed these losses. For the biomass of fish species targeted by fisheries, negative impacts were reversed during a moderate heatwave (28% average difference compared to scenarios lacking a refuge), negated during a strong heatwave (24% difference), and mitigated during severe and extreme heatwaves (21% and 20% respectively). The productivity of fisheries targets was similar with or without a thermal refuge under moderate heatwave conditions, but under strong, severe and extreme heatwaves, refuges became valuable. Average productivity losses were almost negated during strong heatwaves (5% difference), negated during severe heatwaves (17% difference), and mitigated during extreme heatwaves (19% difference). By providing this first estimate of the value of mesophotic reefs as thermal refuges during marine heatwaves we hope to inform conservation and management decisions about the targeted protection of mesophotic reefs.